Особенности следящих методов обработки сигналов измерительных радиосистем - Кречетов В. Ю. (ХНУРЭ, 2012)
Radio engineering tracking system included in the measurement of radio systems operating in conditions of a priori uncertainty of the dynamic effects, which is tracked by setting the signal. Increase in the conditions of prior uncertainty and the dynamic effects of noise on the output of the discriminator tracking accuracy and precision of measurements using these systems, speed, range, angular coordinates, we can by building adaptive tracking systems, adapting to a specific a priori uncertainty.